Khaul and Maqam Thariqath in Sufism: the Analysis of Implementation Inside the Live of Sufi Thariqath Naqshabandiyah at Dawe Kudus Boarding School - Masturin, M (LPPM IAIN Kudus, 2018)
The core of all religions are surrender to The God, as the Creator of all universe. The term of surrender generically called Islam in the Arabic terminology. Personal surrender to God The Ultimate Being, as the most right a part of self religious attitude. This attitude do not consider which any form of the people religious formation. Furthermore, apart form from this religious personality really rejected. According to the conceptualization of religious personality above, the sufism prosecuted to spell out all it’s doctrines related to cultural and social analysis. The sufism assumpt about religious multiculturality as the only form of religion in the world, while the nature it’s similar, that worship in source of anything. The Sufi as they stay in some stage on viewing about God, he will look at Him as essence not as the outer side of His perception. This reasearch stand by qualitative approach. The result of research aim about correlation between religion and society are creates the influence of the two sides. The religion influence the society otherwise the society influence the religion. This reciprocal influences, between the development of society and the improvement of religion, as social and cultural realities that’s need to be wider understand and deep perception.